Research on the Synthesis, Characterization, and Photocatalytic Activity of BiVO₄/g-C₃N₄ and its Application in Treating Ciprofloxacin Antibiotic in Water Environment - Huyen, Dang Thanh; Viet, Nguyen Minh (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 1DO - 10.25073/2588-1140/vnunst.5932, 2025)
In this study, the BiVO 4 /g-C 3 N 4 composite material was successfully synthesized using a combination of the hydrothermal method and calcination, and was applied to the degradation of the antibiotic Ciprofloxacin. The material was characterized by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), Fourier-transform infrared spectroscopy (FT-IR), and UV−Vis diffuse reflectance spectroscopy. The results demonstrated that BiVO 4 /g-C 3 N 4 exhibited the structural, morphological, surface, and optical properties of each individual component. The formation of the BiVO 4 /g-C 3 N 4 heterostructure facilitated more efficient charge transfer and suppressed electron–hole recombination, thereby enhancing the photocatalytic activity compared to pure BiVO 4 and g-C 3 N 4 . Under visible light irradiation, 7 wt% BiVO 4 /g-C 3 N 4 was identified as the optimal composition, achieving a Ciprofloxacin degradation efficiency of 76.45% after 360 survey minutes at pH = 7 and an initial concentration of 10 ppm.